Underground hydrosphere and geofluids of the Earth’s crust and upper mantle - Kudelsky, A.V. (Geofizicheskiy Zhurnal, 2017)
The physicochemical state of the water at various temperature and pressure conditions of the Earth’s interior has been characterized. Two groups of geofluidic systems for water have been established: subcritical (T < 374 ¸ 450 °Ñ) and supercritical (T > 374 ¸ 450 °C), which together with the hydrogeological system of structured waters constitute hydrophysical, hydro- and fluid-geological lithosphere zonation. Based on the systematization of data on the decrepitating of gas-liquid inclusions in minerals of rocks of various facies of metamorphism, as well as fluid manifestations in zones of global rifting, a high content of mineral substances in the composition of dense supercritical fluids and a high electrical conductivity of such fluids is established. Recognition of high “salt content” and high electrical conductivity of supercritical fluids opens new possibilities in interpreting local high-speed anomalies and anomalies of electrical conductivity in the Earth’s crust, revealed from deep seismic and magnetotelluric sounding data. It is shown that with the water condensate — a kind of liquid-phase “restite” from the sphere of supercritical fluids separation — the genesis of highly mineralized waters and brines is connected in the crystalline basement of ancient platforms. On the example of the lithosphere of Belarus, for the first time, deep boundaries of localization of both structured water and supercritical geofluids have been determined. The hydro- and fluid-geological zonation of the lithosphere and upper mantle has been established as a basis for solving the scientific and practical problems of tectonophysics, mineralogy, hydrogeology, genesis and distribution of different type’s minerals, including hydrogenogenic minerals. A thermophysical method for determining the depth and thickness of a zone of underground structured waters is proposed. The method is based on comparison of seismic and thermal characteristics of rocks with sub- and supercritical temperatures for water.